PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN KETERAMPILAN MENULIS BAGI SISWA KELAS 11 DI MI AL-HIJRAH - Salawati, Salawati; Sumarni, Sumarni (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2022)
This study aims to find out an overview of the use of image media in improving writing skills for students II at MI AL-Hijrah, Biringkanaya sub-district, Makassar City. This research method was obtained through observation, interviews and documentation. The data analysis technique used in this research is descriptive and qualitative techniques. The results of this study indicate: the learning process at MI AL-Hijrah, Biringkanaya sub-district, Makassar City, which initially began to feel tedious, began to be overcome by using image media because the use of image media students' understanding of learning began to increase. Evidenced by the interest in the media image changes in the ability of students to make simple pictures in class II increased.